PERANCANGAN SISTEM ALAT PENGENDALIAN PADA KIPAS ANGIN MENGGUNAKAN PIR DAN ARDUINO BERBASIS ANDROID - Dedy Ristanto Hulu; Aditya Perdana; Denny Irvan Sinuhaji; Mardi Turnip (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2019)
A fan is a device for air conditioning, air fresheners and dryers. The use of a fan that has to press the on / off button makes a person lazy to move. This study aims to be one of the efforts with the advancement of technology to provide convenience and comfort through the development of automated tool systems in electronic devices such as fans. The components used for system design are Arduino Uno microcontroller modules, Bluetooth HC-05 modules, PIR (Passive Infrared Receiver) motion sensors and Android-based smart phones, while software design uses the Arduino IDE and Mit Inventor app. Based on the results of the test, the system on the device that was made was able to detect humans within 10 meters and a Bluetooth range of 12 meters to control the fan through a smartphone.